A study on the implementation of talent management practices at Malaysia companies. - Abdul Hamid, Zabeda; Hashim, Junaidah; Omar, Azura; Mustafa Kamil, Bidayatul Akmal (Society for Business Research, 2011)
This research was carried out using method of interview among selected human resource practitioners of six Malaysian companies. This research explores talent management practices particularly on the implementation and the effect of the practices on employee engagement and retention. It was found that talent management is considered as the strategy of organization to retain employees. The strategy involves the human resource activities such as recruitment, selection, training and development and performance management. The engagement and retention talented employees needed in order for an organization to success and improve performance. In highly competitive market, having the right employees is the way to ensure organizational succeed. The impact of this research will create an opportunity to develop talent management strategy. It is expected that the identification and development of talent management strategy would result in additional benefits for the organization and its employees.